2019
DOI: 10.1002/aenm.201901839
|View full text |Cite
|
Sign up to set email alerts
|

Versatile N‐Doped MXene Ink for Printed Electrochemical Energy Storage Application

Abstract: Printing is regarded as a revolutionary and feasible technique to guide the fabrication of versatile functional systems with designed architectures. 2D MXenes are nowadays attractive in printed energy storage devices. However, owing to the van der Waals interaction between the MXene layers, the restacking issues within the printed electrodes can significantly impede the ion/electrolyte transport and hence handicap the electrochemical performances. Herein, a melamine formaldehyde templating method is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
250
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(255 citation statements)
references
References 52 publications
3
250
1
1
Order By: Relevance
“…It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…It is also reported that nitrogen doping is beneficial to enhance the electrical conductivity. Yu et al similarly used melamine as the nitrogen source to realize the crumpled nitrogen‐doped Ti 3 C 2 T x , which showcased a high areal capacitance (70.1 mF cm −2 ) coupled with improved cycling performance, demonstrating a great potential for the heteroatom doping in achieving advanced MXene‐based supercapacitors with high charge storage properties.…”
Section: High‐performance Supercapacitorsmentioning
confidence: 99%
“…Although Akuzum et al study provides insights into the processability of MXenes, the development of printing procedures and ink formulations are still at the early stages; mostly producing flat re-stacked films or single printed layer arrays using techniques such as painting, writing [88], stamping [89], screen printing [90,91] and extrusion [92] and hence not fully utilizing the potentialities of printing in threedimensions. Only recently Yang et al demonstrated for the first time the possibility to print 3D MXene freestanding objects by designing inks composed solely of large, high aspect ratio MXene flakes (8 μm average lateral size and 1-3 layers) and water [93].…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Later, Yu et al designed crumpled N-doped MXene (MXene-N) composite inks for printable electrochemical energy storage devices [91]. By mixing MXene-N with carbon nanotubes (CNT), activated carbon (AC) and GO, they were also able to produce a highly viscous, binder-free hybrid ink with ideal shearthinning features for extrusion printing with controlled thickness.…”
Section: Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation